Farewell to the factory : auto workers in the late twentieth century - Milkman, Ruth, 1954- (University of California Press, 1997)
This study exposes the human side of the decline of the US auto industry, tracing the experience of two key groups of General Motors workers: those who took a cash buyout and left the factory, and those who remained and felt the effects of new technology and other workplace changes.